Understanding the social and cognitive influences on the adoption of COVID-19 non-pharmaceutical interventions: a survey of a Saudi Arabian sample - Alobaydullah, Ahmed; LaJoie, Andrew Scott; Thomas, Susann Denise; Fumey, Raphael; Alsaleem, Abdulrahman (Frontiers in Public Health, 2025)
IntroductionCOVID-19 vaccines prevent death and severe illness, but not infection. Public health leaders continue to stress the importance of non-pharmaceutical intervention behaviors (NPIs). However, little is known about how social, environmental, and cognitive factors influence the adoption of NPIs.MethodsA theory-informed survey was distributed to adults living in Al-Ahsa, Saudi Arabia. The primary focus is self-reported adherence with NPIs. Socio-environmental factors included observational learning, social norms, and media. Personal cognitive factors included self-efficacy, outcome expectancies, and knowledge.ResultsThe mean age was 31 years (n = 368), most participants were males (62%), and the study sample were significantly more vaccinated (40%) than the Saudi public (5.3%). NPIs were strongly correlated with social norms (r = 0.73, p < 0.001), and positively correlated with self-efficacy (r = 0.25, p < 0.001). Females reported higher NPIs adherence rates (M = 17.04, SD = 3.86) than males (M = 16.29, SD = 4.12). The hierarchical multiple regression model revealed that socio-environmental factors explained a significant proportion of variance in NPIs (R2 = 0.52, p < 0.001).DiscussionThe findings highlight the usefulness of a social cognitive model in predicting NPIs. The study shows that social factors, especially social norms, significantly influence the adoption of NPIs. Hence, health organizations should consider social factors when developing campaigns against current and future infectious diseases.